Review: The Origins of the Synagogue. A Socio-Historical Study - Reif, Stefan C. (The journal of theological studies, 2003)
The Origins of the Synagogue. A Socio-Historical Study. Anders Runesson Pp. 573 (Coniectanea Biblical New Testament Series, 37.) Stockholm Almqvist & Wiskell 2001 91 22 01946 4 SEK 366